Getting a dial tone telecommunications liberalisation in Malaysia and the Philippines - Salazar, Lorraine Carlos (Institute of Southeast Asian Studies, 2007)
Analyses the telecom reform process in Malaysia and the Philippines. Looks at the institutions and actors that were the driving force behind these changes, and examines state capacity, market reform, and rent-seeking in the two countries.